Legal Reform on Corporate Responsibility in The Disruption Era (Study of Legal Issuese-Commerce) - Muhammad Husni Fahruddin (JILPR Journal Indonesia Law and Policy Review, 2023)
The speed of technological development has changed the way humans live dramatically, the world is changing very quickly into the "age of disruption." “Big data, artificial intelligence, technology 4.0 have destroyed all definitions, measurements and even theories that have been used as references. At the same time, this age of disruption provides enormous opportunities and also has challenges and problems that were never imagined before, the anti-free market movement has emerged and a protectionist approach is increasingly dominating. With the advent of sophisticated technology, new innovations have emerged to replace old methods that are less effective and efficient. These new innovations are also required to be able to keep up with the needs of society and developments that continue to move forward. This phenomenon is called the era of disruption, this emerges slowly and suddenly can disrupt and replace the old system because it is easier to implement and practical. The era of disruption is an era of innovation and massive change that fundamentally changes all existing systems, arrangements and landscapes to new ways. Entering the era of disruption, companies must be more creative and innovative by creating new strategic and appropriate rules to survive amidst competitive competition. E-Commerce itself is present in society after being influenced by the era of disruption characterized by the increasingly rapid development of information technology, giving rise to a new revolution, namely the transition from conventional work systems to the completely practical digital era. Another thing that often gives rise to legal issues that demand legal reform so that there is protection through legal regulations that regulate company responsibilities in order to achieve legal certainty and prosperity can be realized in an era of disruption.